Lipid and cell wall changes in an inositol-requiring mutant of Neurospora crassa. - Hanson, B (1979)
An inositol deficiency in the inositol-requiring (inl) mutant of Neurospora crassa led to changes in the composition of the inositol-containing lipids and the cell wall. On deficient levels of inositol, phosphatidyl inositol decreased by 23-fold, di(inositolphosphoryl) ceramide decreased by 4-fold, and monoinositolphosphoryl ceramide increased slightly. The inositol deficiency also led to an aberrant hyphal morphology and changes in both the amount of cell wall and the amino sugar content of the cell wall. The glucosamine content of the cell wall decreased by 50%, the galactosamine increased by 50%, but no significant changes were found in the content of the cell wall amino sugar precursors, or in the amino acid, glucose, or total hexose content of the cell wall. Inositol-containing compounds were found associated with purified cell wall material. These compounds were bound tightly to the cell wall but could be removed by treatment with alkali, a treatment which disrupts the cell wall integrity. Possible mechanisms of how changes in lipid composition can affect cell wall biosynthesis are discussed.